Gas mixer identifier of the new ban neonatal incubator - Dávalos Pinto, J (2009)
The objective of this work is to develop a method of Systems Identification applied to the gas mixer in the neonatal incubator BAN, with the aim of finding a mathematical model that describes its dynamics to implement later a controller. The method considered the conduct of an identification nonparametric which was to excite the entrance to the mixer with signals generated by a computer to determine basic information but valuable. Then, the parametric identification was made consisting of excite the entrance to the mixer with a pseudo-random binary signal to obtain the data matrix with which the coefficients were obtained model ARX. The validation and cross correlation conducted showed the effectiveness of the method. Based on the survey results mixer, it is concluded that the subsystem Pipeline Oxygen is the fourth order considering actuators mechanically coupled and transmitter and subsystem Pipeline Air is the fourth order considering the actuator and transmitter.